Why do Open Government Data initiatives fail in developing countries? A root cause analysis of the most prevalent barriers and problems - Alexopoulos, Charalampos; Saxena, Stuti; Janssen, Marijn; Rizun, Nina; Lněnička, Martin; Matheus, Ricardo (Wiley-Blackwell, 2024)
Open government data (OGD) include the provision of government data, which have so far been reserved for the provision of public utilities and services, wherein different stakeholders may create value out of the same source. Recently, OGD initiatives around the world have dampened or were found to be inadequate for one or other reasons. The present study seeks to underline the root causes behind these inadequate or stalled initiatives with a specific focus on the developing countries. This article undertakes a literature review of the most significant studies in this area, followed by a root cause analysis wherein the database across Scopus and Web of Science has been explored with the set inclusion and exclusion criteria being set in line with the research focusing on the hinderances and bottlenecks behind the failure of OGD initiatives (n similar to 15), thus not only summarizing what has been revealed in previous studies but also identifying these "root-cause" relationships, which are responsible for the stalled OGD projects. A deep understanding of the literature on OGD shows that research of OGD barriers repeat each other. The results show that the main root causes include politico-administrative, social, technological, legal and organizational (inter- and intra) dimensions including aspects like state of the economy, infrastructural issues, the tendency to copy the OGD initiative without need to institutionalize the same, and so forth. Whereas a number of studies are available covering the barriers in the roll-out and implementation of OGD initiatives, the root causes behind the existence of these barriers have not been identified so far-the present study seeks to plug this gap. Besides being a contribution to the extant OGD literature in general, the study seeks to leave academic and practical implications for furthering up deliberations and discussions on the OGD themes with specific impetus upon the cause analysis of the failure in OGD initiatives and the manner in which the same may be corrected or preempted.
Proč iniciativy Open Government Data selhávají v rozvojových zemích? Analýza kořenových příčin nejčastějších překážek a problémů
Keywords: barrier; demand-side; Open Government Data; rootcause analysis; supply-side; bariéra; strana poptávky; Open Government Data; analýza kořenových příčin; strana nabídky